Impact of plasma volume status on mortality following left ventricular assist device implantation. Issue 6 (26th December 2020) - Imamura, Teruhiko; Narang, Nikhil; Combs, Pamela; Siddiqi, Umar; Mirzai, Saeid; Stonebraker, Corinne; Bullard, Heather; Simone, Pamela; Jeevanandam, Valluvan
Abstract: Worsening systemic congestion is often the central trigger of hospitalization in patients with heart failure. However, accurate assessment of congestion is challenging. The prognostic impact of systemic congestion following durable continuous‐flow left ventricular assist device (LVAD) implantation remains unknown. Consecutive patients who received durable continuous‐flow LVAD implantation between January 2014 and June 2017 and were followed for 1 year were included. The association of preoperative plasma volume status, which was calculated using patients' body weight and hematocrit and expressed as a deviation from ideal plasma volume, with 1‐year mortality following LVAD implantation was investigated. In total, 186 patients (median 57 years and 138 males) were included. Baseline plasma volume status was −30.1% (−37.1%, −19.4%) on median. Eighty‐eight patients (47%) had higher plasma volume status (>−29.8%), and their 1‐year survival was significantly lower than those without (67% vs. 87%, P  = .001). High plasma volume status was an independent predictor of 1‐year death with an adjusted hazard ratio of 4.52 (95% confidence interval 1.52‐13.5). Baseline systemic congestion, as defined by the high plasma volume status, was associated with higher mortality following durable continuous‐flow LVAD implantation. The implication of improving preoperative plasma volume remains an area of needed investigation. Abstract : Baseline systemic congestion, which was defined by the high estimated plasma volume status calculated using hematocrit and body weight, was associated with higher mortality following durable left ventricular assist device implantation.